Membangun Hubungan antar Agama Mewujudkan Dialog dan Kerjasama - Taslim HM Yasin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
Every religion has its own uniqueness, that distinguish between one religion to another religion. However, the religions have many similarities as well as the great potential that can be developed to build the state and nation. Religious pluralism, in essence, contains the potential of the conflict, as well as containing the potential to build cooperative relationships. It lies the importance of religious life arrangement within a community or country. The dialogue is an important part in problem solving, and is deemed able to solve various problems of religious life, as long as the dialogue participants were able to show the attitude of tolerance and mutual respect.